2013
DOI: 10.1136/neurintsurg-2013-010745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CT and fluoroscopic guidance for lumbar puncture in an obese population with prior failed unguided attempt

Abstract: Both fluoroscopic and CT guidance may be used to perform an LP in an obese population with a short procedure time and low radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 9 publications
4
34
0
Order By: Relevance
“…Congenital spine abnormalities and spinal cord abnormalities (e.g., tethered cord), or local skin infections at the LP site can be contraindications to perform an LP. In case of congenital spine abnormalities, the LP procedure can be guided by fluoroscopy, ultrasound, or computed tomography [1,30–33]. Performing an LP through infected tissue increases the risk of central nervous system infections and reduces the diagnostic value of the LP in case of a suspected central nervous system infection.…”
Section: Resultsmentioning
confidence: 99%
“…Congenital spine abnormalities and spinal cord abnormalities (e.g., tethered cord), or local skin infections at the LP site can be contraindications to perform an LP. In case of congenital spine abnormalities, the LP procedure can be guided by fluoroscopy, ultrasound, or computed tomography [1,30–33]. Performing an LP through infected tissue increases the risk of central nervous system infections and reduces the diagnostic value of the LP in case of a suspected central nervous system infection.…”
Section: Resultsmentioning
confidence: 99%
“…Brook et al 18 showed that both the CT and fluoroscopicguided LP are a useful alternatives with low procedure times and radiation dose in obese patients with prior failed unguided attempts. However, the authors in that study measured the total procedure time but not the actual radiation screening time.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] The added costs of fluoroscopy and US guidance over the standard procedure seem comparable. 10 The benefits, risks, and cost of stratifying morbidly obese patients to an initial USassisted LP in the clinic should be prospectively evaluated. The LP is one of the procedural domains incorporated into the Next Accreditation System recently released by the Accreditation Council for Graduate Medical Education for neurology training.…”
mentioning
confidence: 99%